2007
DOI: 10.1002/app.26250
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of a polyurethane film by low pressure glow discharge oxygen plasma treatment

Abstract: Low pressure oxygen plasma has been used to improve the surface wettability of a polyurethane film. The modifications induced by the plasma treatment in the material were analyzed using contact angle measurements. X-ray photoelectron spectroscopy technique was used for surface characterization of the plasma-treated films. Atomic force microscopy and scanning electron microscopy were used to analyze topography changes due to the plasma-etching mechanism. The results show a much better surface wettability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 81 publications
5
44
0
9
Order By: Relevance
“…Although the oxygen plasma treatment enhances the wetting contrast, it also tends to slightly alter the morphology of creases and the wettability patterns (Fig. S10), probably due to changes in the surface roughness, surface energy, and the mechanical properties of the polyurethane induced by the oxygen plasma (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…Although the oxygen plasma treatment enhances the wetting contrast, it also tends to slightly alter the morphology of creases and the wettability patterns (Fig. S10), probably due to changes in the surface roughness, surface energy, and the mechanical properties of the polyurethane induced by the oxygen plasma (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…2B). The highly reactive oxygen species generated during the low-pressure plasma process are known to react with the various surface groups, generating mostly hydrophilic groups (19) that can reduce an initial surface chemical gradient. We found that the difference in fluorescence peak wavelength between the tops and bottoms of the ridges was significantly removed after the plasma treatment, indicating significant loss of the initial polarity gradient.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, it can be concluded that the plasma attacks C u C bonds in the polypropylene chains to form various carbon oxygen bonds, such oxygen-containing groups are known to substantially improve the hydrophilic properties of polymeric materials. 1, 21,22 Results in Figs. 4 and 5 are, therefore, very desirable.…”
mentioning
confidence: 97%
“…21 A large shift in the O / C ratio is a clear indication that surface functionalization is being induced through the interlock of oxygen based polar species resulting from the interaction of the film surface with the species present in the gas discharge. 22 Figure 5 gives a detailed XPS spectrum of the C 1s peak to allow analysis of the oxygen-containing functional groups formed through polymer-plasma interaction. It is clear that exposure to the pulsed air plasma significantly reduces the C 1s peak at 285 eV.…”
mentioning
confidence: 99%